Desenvolvimento de nanocompósitos de borracha clorobutílica/borracha natural com montmorilonita para aplicação em revestimentos internos de pneus sem câmara de ar - Hermenegildo, Gislaine (My University, 2014)
The aim of this work is combining the properties of chlorobutyl rubber (CIIR) and natural rubber (NR) in a binary blend for applications in tubeless tire inner liner, using organomodified clay - montmorillonite (OMMT) – as a filler, in order to improve barrier properties of the material. For this purpose, the blends should exhibit similar mechanical properties to the reference material, CIIR. Sixteen formulations have been prepared in an internal mixer using 5 and 10 phr (parts per hundred of rubber) of OMMT, in two binary blends: CIIR/NR 80/20 and 60/40. In all samples, the carbon black (CB) content was 50 phr. For comparison bases, CIIR and NR formulations were prepared under the same conditions. Furthermore, four nanocomposites have been prepared in absence of CB. These nanocomposites have presented the lowest results in all analyzis, likely due to the absence of carbon black in these formulations. However, in the presence of carbon black, X-ray diffraction (XRD) and scanning electron microscopy (SEM) results have indicated the intercalation of OMMT by the polymer chains and, hence, a better distribution for both blends. It was also observed a decrease in the Mooney viscosity and, therefore, an improvement in the processability, and a decrease in the curing enthalpy (ΔH), being more accentuated in the formulations containing superior amount of the NR, thus indicating the good interaction and interfacial adhesion between the nanoparticles and the polymer matrix in the presence of carbon black. With regard to the MH and ML no significant differences have been obtained as adding OMMT to the formulations with carbon black. However, the blends have showed a decrease in the maximum torque and this may be attributed to the modifier used in the clay, which acts as a lubricant, resulting in a decrease in the MH and ts2, which is interesting from a technological point of view. These nanocomposites have also presented conservation of the hardness, tensile strength and modulus values at 100 % elongation. On the other hand, the degradation of the polymer matrix in the presence of quaternary ammonium salts has had a negative effect on the thermal performance of the nanocomposites. The barrier properties of blends in the presence of OMMT e CB have not shown significant improvement. However, the good dispersion of the carbon black, the conservation of the property barrier, modulus at 100% and tensile strength before and after the aging, mainly in the system with superior amount of NR (CIIR/NR 60/40), indicate that the blends may be used to the tubeless tire inner liner, without significant change in the mechanical and barrier properties in relation to the reference material, CIIR/CB 100/50, and decreasing the cost of the final product, since the CIIR is 80% more expensive than the NR.
O objetivo deste trabalho é combinar as propriedades da borracha clorobutílica (CIIR) e borracha natural (NR) em uma blenda binária para aplicação em revestimento interno de pneus sem câmara de ar, usando argila organomodificada - montmorilonita (OMMT) - como carga, de modo a melhorar a propriedade de barreira do material. Para este propósito, as blendas devem exibir propriedades mecânicas similares ao material de referência, CIIR. Dezesseis formulações foram preparadas em um misturador interno usando 5 e 10 phr (partes por cem de borracha) de OMMT, em 2 blendas binárias: CIIR/NR 80/20 e 60/40. Em todas as amostras, o conteúdo de negro de fumo (NF) foi 50 phr. Para comparação, as formulações de CIIR e NR foram preparadas nas mesmas condições. Além disso, quatro nanocompósitos foram preparados na ausência de NF. Estes nanocompósitos apresentaram os menores resultados em todas as análises, provavelmente devido à ausência de negro de fumo nestas formulações. No entanto, na presença de negro de fumo, resultados de raios X e microscopia eletrônica de varredura (MEV) indicaram a intercalação da OMMT pelas cadeias poliméricas e uma boa distribuição das partículas em ambas as blendas. Além disso, houve uma redução na viscosidade Mooney e, portanto, uma melhora na processabilidade e uma redução na entalpia de cura (ΔH), sendo mais acentuada nas formulações contendo maior quantidade de NR, indicando assim a boa interação e adesão interfacial entre as nanopartículas e a matriz polimérica na presença de negro de fumo. Em relação ao MH e ML não foram obtidas diferenças significativas à medida que se adiciona OMMT às formulações com negro de fumo. Porém, as blendas mostraram um decréscimo no torque máximo e isto pode ser atribuído ao modificador utilizado na argila, o qual age como um lubrificante, resultando em um decréscimo no MH e no ts2, o que é interessante do ponto de vista tecnológico. Estes nanocompósitos apresentaram ainda manutenção da propriedade de dureza, de tensão na ruptura e módulo a 100 %. Por outro lado, a degradação da matriz polimérica na presença de sais de amônio quaternário influenciou negativamente o desempenho térmico dos nanocompósitos. A propriedade de barreira das blendas na presença de OMMT e NF não mostrou melhora significativa. Porém, a boa dispersão do negro de fumo, a manutenção da propriedade de barreira, de módulo a 100 % e tensão na ruptura antes e após o envelhecimento, principalmente no sistema com maior quantidade de NR (CIIR/NR 60/40), indicam que as blendas podem ser usadas para revestimento interno de pneus sem câmara de ar, sem alteração significativa nas propriedades mecânicas e de barreira em relação ao material de referência, CIIR/NF 100/50, e reduzindo o custo do produto final, uma vez que a CIIR é 80% mais cara que a NR.
Keywords: Borracha; Nanocompósitos (Materiais); Materiais - Testes